Magicians Season 1 Disc 2 - Ralph, Jason; Maeve, Stella; Dudley, Olivia Taylor; MCA Universal Home Video (Firm) (Universal City, CA : Universal, 2016)
Based on Lev Grossman's New York Times bestseller, this centers on Quentin, a brilliant grad student chosen to attend Brakebills University for Magical Pedagogy, a secret upstate New York university specializing in magic. He and his twentysomething friends soon discover that the magical fantasy world they read about as children is all too real, and poses a grave danger to humanity.
Title from container.
Originally broadcast in 2015.
Widescreen (1.78:1)
Includes the episodes: The World in the Walls; Mendings, Major and Minor; Impractical Applications; The Mayakovsky Circumstance; and bonus features.
Bonus features: Deleted scenes; Gag reel; Ther world of the magicians.
Jason Ralph, Stella Maeve, Olivia Taylor Dudley.
Keywords: Magic; Magicians; Supernatural; Fiction; Fantasy; Television Series